New Micellar Electrokinetic Chromatographic Method for Analyzing Idebenone in Pediatric Formulations - Contin, Mario Daniel (2017)
A novel, simple and reliable method based on micellar electrokinetic chromatography with ultraviolet detection was developed to analyze idebenone in a pediatric formulation. Idebenone is a synthetic short chain benzoquinone that acts as an electron carrier in the mitochondrial electron transport chain facilitating the production of adenosine triphosphate. It can be found in two different redox states that differ in their physiological properties. Idebenone has been investigated as a treatment in several neurological disorders like Friedreich's ataxia, Leber's hereditary optic neuropathy, mitochondrial encephalomyopathies and senile dementia. Accordingly, a micellar electrokinetic chromatography was employed to discriminate both redox forms. The final optimized system was validated in terms of selectivity, linearity (r2 0.992), limit of detection (0.5 μg/mL), limit of quantification (1.8 μg/mL), intra- and inter-day precision (RSD ≤ 2) and accuracy in terms of recovery studies (99.3-100.5%). Robustness was studied following a Plackett-Burman design. Finally, the validated system was applied to the analysis of idebenone in a pediatric formulation.